Effect of dietary taurine enhancement on growth and development in red sea bream Pagrus major larvae. (9th September 2014) - Kim, Yang‐Su; Sasaki, Tsukasa; Awa, Masato; Inomata, Maho; Honryo, Tomoki; Agawa, Yasuo; Ando, Masashi; Sawada, Yoshifumi
Abstract: This study investigated the effect of feedings taurine‐enriched rotifers on the growth and development of larval red sea bream (RSB). Rotifers incubated in taurine‐enriched water at a taurine concentration of 800 mg L −1 (T‐800) and 0 mg L −1 (T‐0) were fed to larvae from 3 to 20 days after hatching (DAH). Notochord length, body weight and specific growth rate of T‐800 group were significantly greater than those of T‐0 at 14, 17, 9–11 and 18–20 DAH. Taurine content of larvae in the T‐800 group increased rapidly from 11 DAH and thereafter remained significantly higher than T‐0. Flexion larvae firstly appeared in both groups at 8 DAH, however, at 20 DAH post‐flexion larvae were significantly more abundant in T‐800 than T‐0. While nucleic acid and protein contents (μg mg −1 wet fish) showed remarkable changes, ontogenetic growth in RSB larvae stage was observed to switch from hyperplastic growth to hypertrophic growth with the start of the flexion stage. Although a similar change in nucleic acid contents was observed between the two groups, the protein content (μg fish −1 ) and protein/DNA ratio of T‐800 remained higher than that of T‐0 during the hypertrophic growth period. These results suggest that dietary taurine accelerates the growth and development in RSB larvae especially during hypertrophic growth (flexion stage) after the early hyperplastic growth.